Estimation of malondialdehyde and catalase activity in pregnant women at IIMS&R Hospital, Lucknow, India - Niharika Singh; Saba Khan; Roshan Alam; Mohammad Mustufa Khan; Haseeb Ahsan (Acta Biochimica Indonesiana, 2022)
Background: During pregnancy, the physiological production of reactive oxygen species (ROS) is associated with a variety of maternal, placental, and fetal developmental functions. These functions are disrupted by excessive amounts of ROS, resulting to pregnancy complications. Different stages of pregnancy require a balance between oxidant and antioxidant production. Objective: The aim of this study is to investigate the status of malondialdehyde (MDA) and catalase (CAT) activity in pregnant and age matched non-pregnant women. Methods: In this cross-sectional study, a total of 74 participants were enrolled, including 37 pregnant and 37 age-matched non-pregnant women. The age range of participants was 18 to 40 years. MDA and CAT levels were measured spectrophotometrically. A p-value 0.05 was statistically significant. Results: Compared to non-pregnant women, the mean plasma level of MDA was considerably elevated in pregnant women (p<0.0001). However, the mean level of CAT activity in pregnant women was significantly lower than in non-pregnant women (p<0.0001) In pregnant women, there is a significant strong negative correlation between MDA levels and CAT activity (p<0.01). Conclusion: Pregnant women have high level of oxidative stress, indicating that the pregnant women are more susceptible to oxidative damage and may develop pregnancy-associated complications.